PHACE syndrome: looking backward and forward - Kaizhi Zhang; Shanshan Xiang; Jiangyuan Zhou; Tong Qiu; Yuru Lan; Yi Ji (Orphanet Journal of Rare Diseases)
Abstract PHACE syndrome rarely occurs in patients with infantile hemangioma (IH) but is common in patients with segmental IH involving the head and face. PHACE syndrome involves at least one system abnormality, including arterial abnormalities, structural brain abnormalities, cardiovascular abnormalities, eye abnormalities, and ventral or midline abnormalities. The pathogenesis of PHACE syndrome remains unclear, and it affects various systems in diverse ways. Oral propranolol has good effects on patients with PHACE syndrome. However, there are great challenges in the management of patients with PHACE syndrome in the later stage, including headaches, stroke, neurodevelopment impairment, psychosocial impacts, and poor quality of life. Therefore, this review summarizes the epidemiology, risk factors, pathogenesis, clinical manifestations, diagnosis, treatment, and complications of PHACE syndrome. The latest research on and therapeutic prospects for PHACE syndrome are also discussed.